Application of AI and learning analytics in English education: Benefits and challenges - Muhammad Hasyimsyah Batubara; Luqman MoHa; Agung Yulianto Nugroho; S. Sumihatul Ummah MS; Suhardianto Suhardianto (Yayasan Adra Karima Hubbi, 2024)
Background. The application of artificial intelligence (AI) and learning analytics in United Kingdom education has brought about significant changes in the way students learn and educators teach. The technology offers better personalization of learning and faster feedback, but it also presents challenges, such as resistance from educators and data privacy and security issues. Purpose. This study aims to explore the benefits and challenges of applying AI and learning analytics in the context of United Kingdom language education, with a focus on improving academic outcomes and students' and educators' perceptions of these technologies. Method. This study uses a combined method of qualitative and quantitative approaches. Quantitative data was collected through questionnaires from 100 students and 30 educators, as well as analysis of academic outcomes before and after the application of AI. In addition, in-depth interviews were conducted to gain further perspectives from educators regarding their experiences in using this technology. A case study at a high school in Jakarta was also integrated to enrich the research results. Results. The results showed a significant increase in students' academic outcomes, with the average academic score increasing from 75 to 82 after the application of AI. The increase in positive perceptions of AI is also seen in students and educators, who feel that this technology helps in personalizing learning and improving teaching efficiency. However, challenges such as early resistance from educators and data privacy issues still need further attention. Conclusion. In conclusion, AI and learning analytics have great potential to improve the quality of United Kingdom education, but careful implementation and a deeper understanding of their challenges are necessary for successful long-term implementation.